Improving pedagogical skills in teaching nurses - Annakulova , Saltanat; Zulaykho , Khamraeva (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article examines the importance of improving pedagogical skills in nursing education and the methods for doing so. Although nurse educators often have extensive clinical experience, they frequently lack teaching methodology skills and pedagogical competencies (Espinoza et al., 2021; Ozga et al., 2020)., 2021; Ozga et al., 2020). This study examines the role of innovative teaching methods, specifically simulation training, blended learning, and peer-to-peer learning, in improving pedagogical skills (Paul et al., 2024; Wu et al., 2020). The results show that instructors who have received specialized pedagogical training significantly improve students' knowledge acquisition and practical skills (Shikuku et al., 2024).